Education and Action: Changing Community Sanitation Behavior in Soreang Jipang Village - Tenriawi, Westy (Sociality: Journal of Public Health Service, 2024)
One of the main challenges in improving access to safe sanitation is the low level of public awareness of the health risks posed by dirty water catchment basins. This activity aims to increase community knowledge and awareness of the importance of environmental sanitation, particularly in the construction and maintenance of healthy foul and rainwater harvesting basins. The methods used included lectures, discussions, questions and answers, and hands-on demonstrations involving active community participation. The results of this activity showed a significant increase in community knowledge, skills, and behavior related to environmental sanitation. The community not only understands the importance of healthy water reservoirs, but is also skilled in making and maintaining them. This activity emphasizes the importance of community empowerment as a form of providing information in terms of maintaining the living environment for environmental health and quality of life.